#フィリピンママあるある (#firipinmamaaruaru): (Re)presentations of Motherhood in Japanese-Filipino Children’s TikTok Videos - Tan, Joy Ann Faith F. (Silva Iaponicarum, 2024)
Digital media sites, such as TikTok, are promising spaces that have recently been explored as timely and accessible spaces for analyzing gender, agency, and the wider representation of mixed roots families in Japan. With Japan and the Philippines’ differences in gendered norms, there is an incongruity between the real-life experiences of Japanese Filipino children (henceforth written as JFC) vis-à-vis the gendered expectations and views on motherhood in Japan. This gap is explored through a sample of ten comedic TikTok videos where young JFC users (re)present their Filipino mothers’ identities via the hashtag #firipinmamaaruaru. Using a digital content analysis of their videos, this paper examines JFC’s experiences and perceptions of their Filipino mothers. The analysis shows how Filipino mothers are (re)presented in their children’s videos as bound by the gendered norms of motherhood in Japan. The humor in JFC’s posts points out the reality that their representations of their mothers are not the standard desirable qualities of motherhood as expected in Japan.